Numerical solution of LOx flow in a liquid rocket engine additively manufactured cooling channel - Monokrousos, Nikos; Könözsy, László Z.; Pachidis, Vassilios; Sozio, Ernesto; Rossi, Federico (International Council of the Aeronautical Sciences (ICAS), 2024)
The present work has been conducted in the framework of the DemoP1 demonstrator for the design of a LOx/LNG aerospike engine carried out by Pangea Aerospace. The main objective of the demonstrator is to highlight the central features of the next generation booster-class engines such as reusability, the utilisation of cryogenic coolants and the benefits arising from the ever-growing field of Additive Manufacturing (AM) for high heat flux aerospace applications with increasing thermal load management demands. In the present study a numerical investigation of the cryogenic liquid oxygen coolant flow in an AM cooling channel of the DemoP1 engine is implemented. The simulations are performed on a three-dimensional curvilinear cooling channel of variable, rectangular cross-section of the aerospike engine. Different variations of the two-equation k − ω turbulence model are employed and assessed for the closure of the fluid flow governing equations and the identification of the efficient formulations for the accurate prediction of the spatial development of the primitive variables. The numerical solutions obtained for the characterisation of heat transfer and pressure drop in the AM cooling channel are compared against experimental data provided from Pangea Aerospace for the full-scale single-injector element hot-fire test campaign of the DemoP1 aerospike engine demonstrator.
Keywords: aerospike engine; additive manufacturing; cooling channel; two-equation k −ω turbulence model